Apoferritin as an ubiquitous nanocarrier with excellent shelf life - Dostalova, Simona; Vasickova, Katerina; Hynek, David; Krizkova, Sona; Richtera, Lukas; Vaculovicova, Marketa; Eckschlager, Tomas; Stiborova, Marie; Heger, Zbynek; Adam, Vojtech (International journal of nanomedicine, 2017)
Due to many adverse effects of conventional chemotherapy, novel methods of targeting drugs to cancer cells are being investigated. Nanosize carriers are a suitable platform for this specific delivery. Herein, we evaluated the long-term stability of the naturally found protein nanocarrier apoferritin (Apo) with encapsulated doxorubicin (Dox). The encapsulation was performed using Apo's ability to disassemble reversibly into its subunits at low pH (2.7) and reassemble in neutral pH (7.2), physically entrapping drug molecules in its cavity (creating ApoDox). In this study, ApoDox was prepared in water and phosphate-buffered saline and stored for 12 weeks in various conditions (-20°C, 4°C, 20°C, and 37°C in dark, and 4°C and 20°C under ambient light). During storage, a very low amount of prematurely released drug molecules were detected (maximum of 7.5% for ApoDox prepared in PBS and 4.4% for ApoDox prepared in water). Fourier-transform infrared spectra revealed no significant differences in any of the samples after storage. Most of the ApoDox prepared in phosphate-buffered saline and ApoDox prepared in water and stored at -20°C formed very large aggregates (up to 487% of original size). Only ApoDox prepared in water and stored at 4°C showed no significant increase in size or shape. Although this storage caused slower internalization to LNCaP prostate cancer cells, ApoDox (2.5 μM of Dox) still retained its ability to inhibit completely the growth of 1.5×104 LNCaP cells after 72 hours. ApoDox stored at 20°C and 37°C in water was not able to deliver Dox inside the nucleus, and thus did not inhibit the growth of the LNCaP cells. Overall, our study demonstrates that ApoDox has very good stability over the course of 12 weeks when stored properly (at 4°C), and is thus suitable for use as a nanocarrier in the specific delivery of anticancer drugs to patients.
Keywords: nosiče léků; Drug Carriers; nádorové buněčné linie; Doxorubicin; apoferritiny; Drug Screening Assays, Antitumor; voda; koncentrace vodíkových iontů; doxorubicin-loaded apoferritin; protein nanocarriers; mužské pohlaví; nádory prostaty; screeningové testy protinádorových léčiv; lékové transportní systémy; Cell Line, Tumor; Water; Antineoplastic Agents; Drug Stability; anticancer therapy; encapsulation; doxorubicin; protinádorové látky; Prostatic Neoplasms; Humans; Apoferritins; Hydrogen-Ion Concentration; Drug Liberation; stabilita léku; uvolňování léčiv; long-term stability; Drug Delivery Systems; lidé; Male